Pengaruh Analisis Fundamental, Teknikal dan Overconfidience Terhadap Keputusan Investasi Pada Investor di Wilayah Kabupaten Probolinggo - Mohammad Iskak Elly; Dwi Arif Andreansyah; Tatik Amani (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
The growth of individual investors in Indonesia has experienced a significant surge, due to the considerable potential benefits of investing. The increasing number of investors is inevitably linked to investment decisions, as this relates to the main purpose of investing. Therefore, proper investment analysis and good emotional control are needed. The purpose of this study was to examine the effect of fundamental analysis, technical analysis, and overconfidence partially, simultaneously and to determine the dominant variable on investment decisions in the capital market with the object of this research being investors in the Probolinggo Regency area. This research uses quantitative methods with a causal approach, and the data is collected through questionnaires. The results showed that partially, fundamental analysis of significance 0.19 and overconfidence of significance 0.16 have a significant and positive influence on investment decisions. In contrast, technical analysis does not show a significant and positive influence with a significance level of 0.359. Simultaneously, the variables of fundamental analysis, technical analysis, and overconfidence together have a significant effect on investment decisions with a significant level of 0.00 which does not exceed 0.05. Among the three variables, fundamental analysis has a dominant influence with a standardized coefficient beta value of 0.249